2019
DOI: 10.1177/1120672119897889
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation in esotropic Duane retraction syndrome: Long-term motor outcome of superior rectus transposition

Abstract: Aim: The aim was to evaluate the long-term motor outcome of superior rectus transposition procedure in patients affected by unilateral esotropic Duane retraction syndrome with residual esotropia and anomalous head position. Methods: A retrospective analysis of medical records of patients affected by esotropic Duane retraction syndrome who underwent superior rectus transposition procedure as reoperation for residual esotropia and/or residual anomalous head position. Amount of deviation, anomalous head position,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…We performed SRT in only one patient with residual esotropia which led to successful outcome. In a recent study, Magli et al 19 reported that SRT is an effective surgery in patients with residual esotropia and AHP after unilateral or bilateral medial rectus recession.…”
Section: Discussionmentioning
confidence: 99%
“…We performed SRT in only one patient with residual esotropia which led to successful outcome. In a recent study, Magli et al 19 reported that SRT is an effective surgery in patients with residual esotropia and AHP after unilateral or bilateral medial rectus recession.…”
Section: Discussionmentioning
confidence: 99%
“… 20 As a re-operation for residual esodeviation or residual AHP, in cases with residual AHP despite previous horizontal muscle surgery. 21 To treat cases where abduction limitation is more severe in upgaze than in downgaze (A pattern of motility). 22 To improve alignment and enhance abduction following LR inactivation for severe co-contractions and overshoots in both esotropic as well as exotropic DRS.…”
Section: Pre-operative Considerations Indications and Contra-indications Of Srtmentioning
confidence: 99%
“…As a re-operation for residual esodeviation or residual AHP, in cases with residual AHP despite previous horizontal muscle surgery. 21 …”
Section: Pre-operative Considerations Indications and Contra-indications Of Srtmentioning
confidence: 99%
See 2 more Smart Citations